2017
DOI: 10.1159/000484904
|View full text |Cite
|
Sign up to set email alerts
|

Xia-Yu-Xue Decoction Inhibits Intestinal Epithelial Cell Apoptosis in CCl4-Induced Liver Fibrosis

Abstract: Background/Aims: Intestine-derived endotoxin is thought to play a role in the development of liver fibrosis. However, the pathological change in the intestine during liver fibrosis is still poorly understood. Here, we investigated the effects of Xia-yu-xue decoction (XYXD) on intestinal inflammation, apoptosis, and tight junction integrity in the carbon tetrachloride (CCl4)-induced liver fibrosis. Methods: Murine liver fibrosis was developed by CCI4 treatment three times per week over a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Destruction of TJ-related barrier integrity leads to increased intestinal permeability and increased inflammation (Wen et al, 2014). Previous studies have demonstrated that "Xia-Yu-Xue Decoction" reversed histological changes caused by CCl 4 and restored intestinal barrier integrity (Ma et al, 2017). We found that the expression of occludin and claudin-1 in the rat intestinal tract decreased significantly in CCl 4 -induced liver fibrosis rats, while DOP enhanced the expression of these proteins.…”
Section: Discussionmentioning
confidence: 60%
“…Destruction of TJ-related barrier integrity leads to increased intestinal permeability and increased inflammation (Wen et al, 2014). Previous studies have demonstrated that "Xia-Yu-Xue Decoction" reversed histological changes caused by CCl 4 and restored intestinal barrier integrity (Ma et al, 2017). We found that the expression of occludin and claudin-1 in the rat intestinal tract decreased significantly in CCl 4 -induced liver fibrosis rats, while DOP enhanced the expression of these proteins.…”
Section: Discussionmentioning
confidence: 60%
“…The liver fibrosis mouse model was established referring to the previous report [32]. C57BL/6 male mice of 6-8 weeks old and 20±2 g in weight were supplied by the Experimental Animal Center of Hubei University of Medicine.…”
Section: Ccl4-induced Liver Fibrosis Mouse Modelmentioning
confidence: 99%
“…Furthermore, XYXD has been also reported to play a protective effect in renal injury induced by bile duct ligation (Liu et al 2015). In our previous studies confirmed that XYXD provides prominently anti-liver fibrotic effects in CCl 4 -induced rodents, which attenuated HSCs activation, collagen deposition, and LSECs defenestration (Zhang et al 2014;Ma et al 2017). However, the potential anti-liver fibrosis active constituents and XYXD possible mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 82%
“…In recent years, traditional Chinese medicine (TCM) has become popular for use in the treatment of many liver diseases, such as fibrosis (Zhou et al 2014;Ma et al 2017). Xiayuxue decoction (XYXD), a famous traditional Chinese herbal formulation consists of Rheum palmatum Linn (Polygonaceae), Prunus persica (Linn) Batsch (Rosaceae), and Eupolyphaga sinensis Walker (Corydiidae) was first found in Synopsis of the Golden Chamber in 200 AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation